The Audacious Raconteur Sovereignty and Storytelling in Colonial India - Prasad, Leela (Cornell University Press, 2022)
Can a subject be sovereign in a hegemony? Can creativity be reined in by forces of empire? Studying closely the oral narrations and writings of four Indian authors in colonial India, The Audacious Raconteur argues that even the most hegemonic circumstances cannot suppress "audacious raconteurs": skilled storytellers who fashion narrative spaces that allow themselves to remain sovereign and beyond subjugation. By drawing attention to the vigorous orality, maverick use of photography, literary ventriloquism, and bilingualism in the narratives of these raconteurs, Leela Prasad shows how the ideological bulwark of colonialism-formed by concepts of colonial modernity, history, science, and native knowledge-is dismantled. Audacious raconteurs wrest back meanings of religion, culture, and history that are closer to their lived understandings. The figure of the audacious raconteur does not only hover in an archive but suffuses everyday life. Underlying these ideas, Prasad's personal interactions with the narrators' descendants give weight to her innovative argument that the audacious raconteur is a necessary ethical and artistic figure in human experience. Thanks to generous funding from Duke University, the ebook editions of this book are available as Open Access volumes from Cornell Open (cornellpress.cornell.edu/cornell-open) and other repositories.